Modélisation en apprentissage des langues médiatisé : quelle utilité ? - Jean-Claude Bertin (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The recurrence in the scientific literature of such generic terms as "technology", "computers", etc., creates an ontological illusion: the epistemological unity of CALL is challenged by the wide variety of artifacts, contexts and practices. One may therefore wonder how to deal with the field globally while at the same time taking into account the specificities of local situations. The author suggests models can be an answer for both researchers and language teachers. He explains his theoretical stance and uses two cases to show the heuristic value of the model he has developed.